Comparative Study of User Experience Evaluation Techniques Based on Mouse and Gaze Tracking - Aviz, Igor Leonardo; Souza, Kennedy Edson; Ribeiro, Elison H. B.; Mello Junior, Harold de; Seruffo, Marcos César da R. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Monitoring techniques have been used in the most diverse systems to evaluate user experience. Specifically inWeb environments, techniques such as mouse tracking and eye-tracking generate interaction data that can be analyzed and used for layout and usability improvements. In this context, the present article proposes to analyze and confront the data obtained with the tools Artificial Intelligence and Mouse Tracking-based User eXperience Tool (AIMT-UXT), to collect the data of mouse-tracking, and SearchGaze.js, which is used during the collection of eye-tracking data and eye gaze fixed points. In addition, heat maps are used to verify whether eye tracking follows mouse tracking.